An acoustic analysis of the monophthongs of Penang Malay / Muhamad Farid Abdul Latiff - Muhamad Farid , Abdul Latiff (2020)
The study aims to examine acoustically the production of monophthongs of Penang Malay by five (5) selected female participants who are of the Jawi Peranakan community. Two (2) female participants of Standard Malay were also selected as a comparator to Penang Malay. The first research question focuses on the acoustic features of Penang Malay and Standard Malay based on their formant frequencies of F1 and F2, while the second research question examines the similarities and differences between Penang Malay and Standard Malay based on their acoustic properties. The target vowels are: [a], [i], [u], [ɛ], [ɔ], [ə], [e], and [o]. A series of words were used in eliciting data from the participants. The tokens produced by the participants were recorded and analyzed based on the Formant Frequency Model. The findings reveal that the participants of Penang Malay generally did not distinguish between [ɛ] and [e] and conflated them as one vowel. The findings also suggest that Penang Malay and Kedah Malay are not homogenous as claimed by past researchers.